SOME REFLECTIONS ON THE LINGUOCULTURAL FEATURES OF PHRASEOLOGICAL UNITS IN THE NOVEL "QIYOMAT" - Aybibi Rakhimbayevna Iskandarova (Sciental Journals Publishing, 2025)
This article discusses the characteristics of Russian-Uzbek phraseological units within a parallel corpus, the cases of interpretation during the translation process, their forms as collocations and clauses, as well as their combinations within sentences. It also presents considerations on the development of a literary text corpus for machine translation, the enrichment of machine memory with linguocultural units, and the synthesis of texts in the source and target languages, including morphological synthesis and the construction of syntactic structures.
Keywords: parallel corpus, phraseological unit, collocation, characteristic features, phraseological units in the form of word combinations and sentences, text synthesis, morphological models, tagging.